2021
DOI: 10.1128/mbio.02786-21
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Cell Wall-Recycling l , d -Carboxypeptidase Determines β-Lactam Susceptibility and Morphogenesis in Acinetobacter baumannii

Abstract: To grow efficiently, resist antibiotics, and control the immune response, bacteria recycle parts of their cell wall. A key step in the typical recycling pathway is the reuse of cell wall peptides by an enzyme known as an l , d -carboxypeptidase (LDC). Acinetobacter baumannii , an “urgent-threat” pathogen causing drug-resistant sepsis in hospitals, was previously thought to lack this enzymatic activity due to absence of a known LDC homolog.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 81 publications
(131 reference statements)
0
13
0
Order By: Relevance
“…Growth curves for the wild-type parental strain and ΔLdt Ab and ΔLdt Ab +PBP1b­(S/A) mutants were very similar in the logarithmic phase of growth; however, in the stationary phase both mutants grew slightly slower (in the order: ΔLdt Ab +PBP1b­(S/A) slower than ΔLdt Ab ) and had lower CFU/mL than the parental strain (Figure ). In a recent publication, it was also shown that the ΔLdt Ab mutant of A. baumannii ATCC 17978 had a similar growth rate as the parental strain . In contrast, growth of the ΔLdt Ab +ΔPBP2 mutant of A. baumannii CIP 70.10 was affected more dramatically.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Growth curves for the wild-type parental strain and ΔLdt Ab and ΔLdt Ab +PBP1b­(S/A) mutants were very similar in the logarithmic phase of growth; however, in the stationary phase both mutants grew slightly slower (in the order: ΔLdt Ab +PBP1b­(S/A) slower than ΔLdt Ab ) and had lower CFU/mL than the parental strain (Figure ). In a recent publication, it was also shown that the ΔLdt Ab mutant of A. baumannii ATCC 17978 had a similar growth rate as the parental strain . In contrast, growth of the ΔLdt Ab +ΔPBP2 mutant of A. baumannii CIP 70.10 was affected more dramatically.…”
Section: Resultsmentioning
confidence: 93%
“…In a recent publication, it was also shown that the ΔLdt Ab mutant of A. baumannii ATCC 17978 had a similar growth rate as the parental strain. 37 In contrast, growth of the ΔLdt Ab +ΔPBP2 mutant of A. baumannii CIP 70.10 was affected more dramatically. We observed a significant (∼5fold) decrease in the number of viable cells during the first two hours of incubation.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…While this study was in progress, two other groups reported a characterization of ElsL as a cytoplasmic ld -carboxypeptidase ( 67 , 68 ). Our results here support this conclusion.…”
Section: Resultsmentioning
confidence: 98%